Nurses' Knowledge Regarding Oxygen Therapy; a Cross-Sectional Study - Hassanzad, Maryam; Ghaffaripour, Hosseinali; Rekabi, Mahsa; Mirzendehdel, Mahsa; Sadati, Elham; Elahimehr, Nasrin; Derakhshanfar, Hojjat (Archives of Academic Emergency Medicine, 2022)
Introduction: Oxygen therapy, if done correctly, can save patients' life promptly. However, improper use will be just as dangerous. The present study aimed to investigate the level of nurses’ knowledge on properly using oxygen. Method: This was a cross-sectional study with a minimum sample size of 72 nurses who were randomly selected from various wards of Masih Daneshvari Hospital, Tehran, Iran. To determine the level of knowledge about oxygen therapy, a questionnaire was used to collect data. This questionnaire consists of seven items, each of which is designed to determine the level of the individual’s knowledge about the various details of oxygen therapy. Results: Seventy-eight nurses with the mean age of 35.80±7.42 years participated in the study (87% female). The mean knowledge score of nurses regarding oxygen therapy was 8.89 ± 2.79 out of 16 points. 84.6% of the nurses were able to differentiate various types of oxygen masks. Accordingly, 94.9% of nurses had good knowledge on oxygen humidification. Also, 50% of the nurses had sufficient knowledge about the amount of oxygen flow produced by different masks. 10.3% of the nurses could choose the most appropriate mask for different clinical conditions. 6.4% of the nurses had knowledge of working with flowmeters, and 15.4% of the nurses had sufficient information about the maximum level of oxygen required for the patient. 17.9% of the nurses were familiar with measuring the appropriate amount of oxygen for patients. There was no statistically significant relationship between age (p = 0.57), gender (p = 0.09), employment status (p = 0.38), workplace (p = 0.86), current position (p = 0.11), degree (p = 0.27), and graduation time (p = 0.58) of nurses with good knowledge of using oxygen. However, a statistically significant relationship was reported between nurses' related work experience and their knowledge of the proper use of oxygen (p = 0.03). Conclusion: In general, the nurses’ knowledge at Masih Daneshvari Hospital on how to properly use oxygen is at a moderate level. Nurses' knowledge in some areas, such as working with the flowmeter, choosing the suitable mask for specific clinical conditions, and the maximum oxygen required for patients, is meager and requires training intervention.